Esapidearen gramatika funtzionala (egokitasunaren teoriarako) - Osa, Eusebio (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1993)
In this article, within the Relevance Theory framework, we examine several funcionalist authors and schools in syntax and pragmatics in the last decades (The Prague School, Kuno, Fuley and Van Valin, Halliday, Grice, etc.) in order to establish the specific features of relevance in Basque. Such features turn out to be free word and phrase order, focalization and multiple agreement which allows the possibility of having null arguments.